N.A. Vel’jaminov – surgeon, public health organizer and founder of the first Russian surgical journal (1855–1920) (for the 135th anniversary of the journal «Grekov’s Bulletin of Surgery») - S. F. Bagnenko; S. M. Lazarev (Вестник хирургии имени И.И. Грекова)
The  article  is  dedicated to  the  memory   of  the  Russian  surgeon,  prominent scientist, public  health   organizer and   the founder  of the  first Russian periodical  surgical  journal  of N. A. Vel’jaminov  in 1885,  who  was  born  165  years ago  and died  100  years ago.